AKTIVITAS AKTINOMISETES DARI BANGKA-BELITUNG KOLEKSI BIDANG MIKROBIOLOGI, PUSLIT BIOLOGI- LIPI DALAM MEMPRODUKSI ENZIM KITINASE - Soeka, yati Sudaryati; Triana, Evi; Setianingrum, Ninu (Jurnal Teknologi Lingkungan, 2010)
The aim of the research was to know the capability of actinomycetes isolate from Bangka Belitung, which stored at Microbiology-LIPI Culture Collection, in producing chitinase enzyme. This isolate which could produce chitinolitic enzyme, signed by clear zone at medium contain 1% chitine. The chitinase activity of the isolate which incubated for 1-7 days in the room temperature was analyzed by spectrophotometer in λ 584 nm. The result of this experiment was highest chitinase activities with incubated for 3 days, were 1.66 . 10-2 U/ml. Maximum chitinase activities was found at 1% starch soluble substrate 2.83 . 10-2, pH 8.0 and at 50°C condition were 9.3 . 10-2 and 12.98 .10-2 U/ml respectively.Key words : chitinase, clear zone, spectrophotometer